2000
DOI: 10.1161/01.cir.101.11.1255
|View full text |Cite
|
Sign up to set email alerts
|

Enoximone Echocardiography for Predicting Recovery of Left Ventricular Dysfunction After Revascularization

Abstract: Background —The possibility that enoximone, a nonglycoside, noncatechol, positive inotropic agent, in combination with 2-dimensional echocardiography may predict recovery of myocardial dysfunction after revascularization has not been yet evaluated. Methods and Results —Forty-five patients with chronic coronary artery disease and left ventricular dysfunction underwent dobutamine (DE, 5 to 10 μg · kg −1 · min −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
2
18
0
1
Order By: Relevance
“…These results are consistent with the theoretical background and the results of studies of post-infarction patients [3,4]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are consistent with the theoretical background and the results of studies of post-infarction patients [3,4]. …”
Section: Discussionsupporting
confidence: 91%
“…Another study used enoximone echocardiography to predict functional recovery after myocardial revascularisation, and found that it was more sensitive and had a greater negative predictive value than dobutamine, and also induced fewer hemodynamic alterations [4]. Finally, enoximone has been combined with very low-dose dobutamine in order to detect myocardial viability in the infarcted myocardium of patients with severe heart failure and life-threatening arrhythmias [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least two drugs have these proprieties: the dobutamine, a synthetic β1 agonist with additional α1- and β2-stimulating properties and the enoximone that inhibits cyclic adenosine monophosphate-specific phosphosdiesterase [6,7]. Routinely, the dobutamine is the most common stressor used, whereas the enoximone is particularly useful in patients on beta-blocker therapy [7,8]. The mechanism by which dobutamine stimulation elicits a contractile response in hypoperfused dysfunctional segments without precipitating ischemia has been demonstrated by Sun et al [6].…”
Section: Introductionmentioning
confidence: 99%